Evaluation of the microplastics in bivalves and water column at Pantai Teluk Likas, North Borneo, Malaysia - Nur Nashrah Abd Rahman; Nurzafrah Mazlan; Sarah Syazwani Shukhairi; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Haniza Harun; Afaf Baktir (Springer Berlin Heidelberg, 2024)
Microplastics (MPs) are a pervasive pollutant in the marine environment. Pantai Teluk Likas in Sabah, Malaysia is one of the most visited beaches where tourism, recreational, and fsheries activities are high in this area. Hence, the area sufers from severe pollution, particularly from plastics. This study aims to quantify the microplastic composition in terms of color, shapes, and polymer types in marine bivalves (Anadara granosa, Glauconome virens, and Meretrix lyrata) and water column samples from Pantai Teluk Likas. All samples were digested using sodium hydroxide (NaOH) and incubated in the oven for at least 48 h. Serial fltration was done for each sample before they were observed under the dissecting microscope. The microplastics were identifed and counted based on their physical attributes which were colors and shapes. The functional group of the polymers was determined using FTIR spectroscopy. Microplastics were found present in all samples collected. G. virens had the highest abundance of microplastics at 113.6±6.5 particles/g followed by M. lyrata at 78.4±3.7 particles/g. On the contrary, A. granosa had the least microplastics with an abundance of 24.4±0.6 particles/g. Meanwhile, 110.0±36.2 particles/L of microplastics were found in water column samples from Pantai Teluk Likas. Based on the analysis, fbers were the most common shape in bivalves, while fbers and flms were common in the water column. In terms of colors, black, blue, and red were a few of the most abundant colors observed in both samples. The most common polymer detected in all bivalve species and water column samples is polycarbonate (PC), followed by polymethyl methacrylate (PMMA). Future study that focuses on the correlation between microplastic abundance in the marine biota and the water column is recommended to better understand microplastic availability and exposure.